Розвиток управління бізнес-процесами шляхом імітаційного моделювання - Свірський, Юрій Васильович (Національний університет «Львівська політехніка», 2025)
Дисертаційна робота присвячена удосконаленню існуючих і розробленню нових теоретичних і методико-прикладних положень щодо розв’язання проблем розвитку управління бізнес-процесами шляхом використання імітаційного моделювання, встановлення рівня їхнього дослідження вченими-економістами, виділення питань, які досі не знайшли достатнього висвітлення в економічній науці. The dissertation is dedicated to improving existing and developing new theoretical and applied positions related to solving problems in the development of business process management (BPM) through the using of simulation modeling, establishing the level of their research by economists, and highlighting questions that have not yet received sufficient coverage in economic science. In the first chapter, "Theory and Practice of Business Process Management through Simulation Modeling," the characteristics of the development of business process management are identified, the peculiarities of using simulation modeling as a tool for developing enterprise business process management are revealed, and the principles of business process management development based on simulation modeling are outlined.
Development of business process management through simulation modeling
Keywords: управління бізнес-процесами, моніторинг, розвиток, системний підхід, показники, ефективність, управлінські рішення, імітаційне моделювання, business processes management, monitoring, development, systematic approach, indicators, efficiency, managerial decisions, simulation modeling; 339.137.2:658.511